Target Costing for Accurate Production Costing in a Village Meatball MSME - Melinda Sindy Lorenza; Sarwenda Biduri (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in village economies, yet many rely on traditional cost calculations. Specific Background: Kedai Bakso Gede 5758 in Tenggulunan Village determines selling prices using only raw material and direct labor costs, excluding overhead and distribution expenses. Knowledge Gap: This practice results in understated production costs and imprecise pricing decisions, indicating the absence of comprehensive cost classification in daily operations. Aim: This study analyzes production costs using the target costing method to obtain more accurate cost information and appropriate selling prices. Results: The calculated production cost per portion using target costing is Rp 5,937, higher than the shop’s calculation of Rp 5,500, due to inclusion of factory overhead and delivery costs. The resulting target selling price is Rp 7,718, compared to the current price of Rp 7,000. Novelty: The study demonstrates how target costing can be practically applied in a village culinary MSME with detailed daily production data. Implications: Proper cost classification supports better pricing decisions and cost awareness for village-based MSMEs.